Systematic review: Telehealth in the Patients Management with Heart Failure - Gustian, Citra Indra; Nursalam; Qur'aniati , Nuzul (Universitas Nahdlatul Ulama Surabaya, 2023)
A recurrence of heart failure can lead to rehospitalization. Therefore, it is necessary to have a prevention strategy that aims to reduce mortality and the recurrence of heart failure by minimizing physical contact. Telehealth is an alternative for providing health services to heart failure patients by minimizing mobilization and treatment costs. This research aimed to evaluate the effectiveness of implementing telehealth in the management and care of patients with heart failure. This study used the systematic review method. There were four stages in this study, namely identifying sources, determining eligibility, screening, and deciding which to be reviewed. Literature selection used the PRISMA approach from 4 databases such as ScienceDirect, Google Scholar, PubMed, and Scopus, with inclusion criteria including articles with a period of less than 5 years (2018-2023), free full text, article reviews, and articles using English and Indonesia. Searching results from 4 databases found 43,846 articles. After screening based on the specified criteria, there were 9 articles reviewed. Of the 9 articles, there were 3 that stated that telehealth can reduce the cost of treating heart failure. 3 articles stated that the health status of heart failure patients improved when using the telehealth system. 2 articles stated that telehealth can be implemented by telephone or nursing telephone support to monitor the condition of heart failure patients remotely. Another article stated that telehealth can improve the quality of life of patients with heart failure. It is necessary to implement telehealth in health services to reduce the frequency of readmissions and to make it easier for health workers to monitor patients, especially those with heart failure.